Implementasi Bahasa Indonesia dalam Manajemen Perkantoran: Studi Kasus pada Efektivitas Komunikasi dan Kinerja Organisasi - Agung, Astrid Nayla Putri; Widiyanti, Diah Anugrah; Maulina, Maryam; Rahmatiana, Raisa; Anggraeni, Tiffany Yesha; Rizkyanfi, Mochamad Whilky (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to investigate the implementation of Indonesian in office management, with a focus on case studies on communication effectiveness and organizational performance. This research was conducted using a qualitative research method with a case study method. The determination of the research subject was carried out using the pusposive sampling technique, which is a technique for determining the subject using certain criteria. Data collection is carried out directly by conducting observations and interviews. Data analysis is carried out qualitatively consisting of data reduction, data presentation and conclusion drawing. The results of the study show that consistency in the good and correct use of Indonesian is very much concerned by professionals at various levels. The good and correct use of Indonesian not only reflects professionalism, but also strengthens the effectiveness of communication and builds a positive professional image. However, there are still several challenges in the application of the Indonesian language, such as the influence of technology and globalization, as well as differences in educational backgrounds. To overcome these challenges, education and coaching efforts are needed from management to employees.